The Impacts of Communication in Transformational Leadership and ICT on Customer Satisfaction in the Educational Sector - Elfindah Princes; Tita Rosita; Rais Hidayat (Jurnal Komunikasi dan Bisnis, 2022)
This research aims to assess the impacts of implementing Transformational Leadership (TL) and Information Communication and Technology (ICT) in the education sector to increase Customer Satisfaction especially during uncertainties and in pandemic situations. Using the quantitative approach, this research argues the importance of customer satisfaction in education influenced by the communication skills implemented in Transformational Leadership and ICT. The research setting is in a private school located in Jakarta. Data from 286 respondents using stratified data sampling are gathered and analysed using SMART PLS. The results showed that TL has a stronger influence than ICT in improving customer satisfaction with a value of 0.547 and 0.329, respectively, especially to overcome problems in the learning process during pandemic times. Therefore, we can conclude that both Transformational Leadership and ICT are vital to increase Customer Satisfaction with a higher strength on Leadership. This study indicates the importance of Communication to build relationships in Transformational Leadership to improve Customer Satisfaction in education. Customer Satisfaction is also an essential focus in education, and the correct type of Leadership is needed. With transformational Leadership and the application of ICT, educational institutions can provide better service and, as an implication, can improve Customer Satisfaction.